Current and up-and-coming pharmacotherapy for obsessive-compulsive disorder in adults. (22nd September 2018) - Grassi, Giacomo; Pallanti, Stefano
ABSTRACT: Introduction : Only 40–60% of obsessive-compulsive patients respond to first line treatments, such as selective serotonin reuptake inhibitors (SSRIs) and cognitive-behavioral therapy. Several second-line treatments have been investigated in the last two decades, and most of them seem to work, at least in a subset of patients. However, since there is still a lack of treatment predictors, the treatment of obsessive-compulsive disorder (OCD) is still empirical and non-evidence based. Areas covered : In this paper, we review current and up-and-coming pharmacotherapy for OCD in adults, focusing on two emerging fields of research, inflammation and glutamate systems, since they have attracted the greatest attention in recent years in OCD pharmacological research. Expert opinion : Most of the investigated second-line agents seem to work at least in a subset of patients with OCD. These results raise an open question: what works for who? In our opinion, this question should be answered in a precision medicine perspective or, in other words, individualizing diagnostic processes and treatment approaches. In a precision medicine approach, OCD treatment should be sub-type specific, phase specific, multimodal and sequential, and, more importantly, dimensional.